Yokukansan, a Traditional Japanese Medicine, Adjusts Glutamate Signaling in Cultured Keratinocytes. (16th September 2014) - Wakabayashi, Maki; Hasegawa, Toshio; Yamaguchi, Takuji; Funakushi, Naoko; Suto, Hajime; Ueki, Rie; Kobayashi, Hiroyuki; Ogawa, Hideoki; Ikeda, Shigaku
Abstract : Glutamate plays an important role in skin barrier signaling. In our previous study, Yokukansan (YKS) affected glutamate receptors in NC/Nga mice and was ameliorated in atopic dermatitis lesions. The aim of this study was to assess the effect of YKS on skin and cultured human keratinocytes. Glutamate concentrations in skin of YKS-treated and nontreated NC/Nga mice were measured. Then, glutamate release from cultured keratinocytes was measured, and extracellular glutamate concentrations in YKS-stimulated cultured human keratinocytes were determined. The mRNA expression levels of NMDA receptor 2D (NMDAR2D) and glutamate aspartate transporter (GLAST) were also determined in YKS-stimulated cultured keratinocytes. The glutamate concentrations and dermatitis scores increased in conventional mice, whereas they decreased in YKS-treated mice. Glutamate concentrations in cell supernatants of cultured keratinocytes increased proportionally to the cell density. However, they decreased dose-dependently with YKS. YKS stimulation increased NMDAR2D in a concentration-dependent manner. Conversely, GLAST decreased in response to YKS. Our findings indicate that YKS affects peripheral glutamate signaling in keratinocytes. Glutamine is essential as a transmitter, and dermatitis lesions might produce and release excess glutamate. This study suggests that, in keratinocytes, YKS controls extracellular glutamate concentrations, suppresses N-methyl-D-aspartate (NMDA) receptors, and activates glutamate transport.